Annual net CO2 fluxes from drained organic soils used for agriculture in the hemiboreal region of Europe - Bārdule, Arta; Laiho, Raija; Jauhiainen, Jyrki; Soosaar, Kaido; Lazdiņš, Andis; Armolaitis, Kęstutis; Butlers, Aldis; Čiuldienė, Dovilė; Haberl, Andreas; Kull, Ain; Muraškienė, Milda; Ostonen, Ivika; et al. (Copernicus Publications, 2025)
Carbon dioxide (CO2) emissions from drained organic soils used for agriculture contribute significantly to the overall anthropogenic greenhouse gas budget in the land use, land use change, and forestry (LULUCF) sector. To justify the implementation of climate change mitigation measures on these lands, it is important to estimate at least the regional variation in annual net CO2 fluxes. This study presents the first estimates of annual net CO2 fluxes from drained nutrient-rich organic soils in croplands (8 sites) and grasslands (12 sites) in the hemiboreal region of Europe, represented by Estonia, Latvia, and Lithuania. The study sites represented both deep and shallow highly decomposed, organic soils, categorised based on the concentration of organic carbon in the top 20 cm soil layer. CO2 flux measurements were conducted over at least 2 years at each site. To estimate annual net CO2 fluxes, ecosystem respiration (Reco) and soil heterotrophic respiration (Rhet) were measured using a manual dark-chamber technique, and carbon (C) input into soil through plant residues was estimated. Reco was strongly dependent on temperature, particularly soil temperature at 10 cm depth, but was rather independent of the soil water table level and soil moisture. The overall mean annual net soil CO2 fluxes, calculated as the difference between annual output (Rhet) and input (plant residues), were 4.8 ± 0.8  for croplands and 3.8 ± 0.7  for grasslands, while the means for “true” or deep organic soil were 4.1 ± 0.7  in croplands and 3.2 ± 0.6  in grasslands (mean ± standard error). Both the annual Reco and net CO2 fluxes for shallow highly decomposed organic soils, currently not recognised as organic soil by the Intergovernmental Panel on Climate Change (IPCC), were of similar magnitude to or even higher than those from deep organic soil, suggesting a need to separate them from mineral soils in emission estimation.
Keywords: turvemaat; turvepellot; kasvihuonekaasut; drained organic soils; agriculture; climate changes